PERKEMBANGAN KEBUDAYAAN DALAM KERAJAAN ACEH DARUSSALAM - ,, Marsus (Historia Islamica: Journal of Islamic History and Civilization, 2022)
The cultural development of a kingdom has become a necessity of its existence. It can also be interpreted as an attempt by the kingdom to show its existence in the world political arena. The Kingdom of Aceh Darussalam experienced cultural development as an effort to introduce the culture of the archipelago and Islam. These two things make the culture of the kingdom of Aceh Darussalam have different cultures from the cultures of other kingdoms, such as religious, political and trade cultures. In addition to the form of culture, there are also cultural products in the form of physical and non-physical, namely infrastructure and intellectuality. What is interesting is that these cultures were born from acculturation between religious teachings, customs and intellect, so that the unification of Aceh Darussalam's culture can be used as the identity of a kingdom.